Przebieg i realizacja programu SAPARD w regionie północno-zachodnim - Zajdel, Małgorzata (The Course and Realization of SAPARD Programme in the North-West Region, 2006)
The objective of the elaboration is an analysis of a course and an implementation of operating programme in the north-west region. The analysis shows that the programme was introduced with delay and it was necessarily modified with some proposed solutions. Farmers were the most interested in investments and the purchase of tractor. The programme played the part as a new instrument of agriculture financing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 529-534